Biosynthesized silver nanoparticles: Decoding their mechanism of action in Staphylococcus aureus and Escherichia coli - Quinteros, Melisa de los Ángeles (2018)
The oxidative stress generation in bacteria by the presence of antibiotics (in this case silver nanoparticles (AgNPs)) is already widely known. Previously, we demonstrated that AgNPs generate oxidative stress in Staphylococcus aureus and Escherichia coli mediated by the increase of reactive oxygen species (ROS). In this work we are demonstrating the consequences of the oxidative stress by the presence of AgNPs; these bacterial strains increased the levels of oxidized proteins and lipids. In addition, it was possible to determine which reactive oxygen species are mainly responsible for the oxidative damage to macromolecules. Also, we found that the bacterial DNA was fragmented and the membrane potential was modified. This increase in the levels of ROS found in both, S. aureus and E. coli, was associated with the oxidation of different types of important macromolecules for the normal functioning of cell, so the oxidative stress would be one of the mechanisms by which the AgNPs would exert their toxicity in both strains, one Gram positive and the other Gram negative of great clinical relevance.